# How is this possible: 1^2 - 1^2 =1^2 - 1^2 1x1 - 1x1 = (1+1)(1-1) [:-a^2- b^2= (a-b)(a+b)] 1(1-1) =(1+1)(1-1) 1=[(1+1)(1-1)]/(1-1) 1=(1+1) 1=2

2
by devraj

2014-12-04T00:02:57+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
The error is in the 4th step... in which u are dividing the RHS by (1-1) which is 0,
You cannot divide it by zero as the value becomes non-determined value..
but both the (1-1) gets cancelled
you cannot carry on with calculations with a value which is not defined
but (1-1)/(1-1)= 1 if (1-1)is taken as any variable you would cancel it
(1-1)is not a variable... its like this.. u can prove 2 =7.. 1st consider the equation, multiply both sides by 0, u'l get 0=0.. LHS=RHS hence 2=7.. but its wrong.. u cannot multiply or divide with zero..
thanx for explaining
2014-12-04T00:20:08+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
1^2 - 1^2 =1^2 - 1^2
1x1 - 1x1 = (1+1)(1-1) [:-a^2- b^2= (a-b)(a+b)]
1(1-1) =(1+1)(1-1)
1(0) = 2(0)
0 = 0 //Hence, possible//

First of all, you need to solve the values on one side(say, LHS) and then may compare it with the resultant value of the other side(RHS) for further solving.
And so in this case, you need to subtract 1 from 1 on either sides first, multiply the difference with 1 and 2 respectively and then consider the resultant "0"s for equaling.
Hence, possible !